THE IMPLEMENTATION OF PHOTOGRAPHS IN IMPROVING STUDENTSâ€™ SPEAKING ABILITY - Ulfah Fauziah Alfalah; Anne Ratna Suminar (English Education and Applied Linguistics Journal (EEAL Journal), 2020)
The title of this research is â€œTHE IMPLEMENTATION OF PHOTOGRPHS IN IMPROVING STUDENTSâ€™ SPEAKING OF STORYTELLINGâ€. The purpose of this study was to investigate the studentsâ€™ speaking storytelling using photographs. The research explored about photograph in teaching speaking of storytelling. The method that applied in this research was quantitative method which was preexperimental design. Speaking test and questionnaire were used to collect the data. This research was conducted to 1st grade student in a private senior high school in Garut. Based on the result of this research, it was shown that photographs affected in improving speaking skill ability. It was proven of the different score in pre-test and post-test score. The post-test score increase significantly and it also could be concluded from the t-test result in which t-observed was higher that t-critical it meant there was significant affect in improving studentsâ€™ speaking ability using photographs. It was said that Ho was accepted if the lower has negative (-) value and upper has positive (+) value or sig. (2-tailed) > Î±. From the table above it was showed that the lower and upper had negative (-) value and sig. (2-tailed) = 0.000